2002
DOI: 10.1046/j.1365-2958.2002.02822.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of multiple var genes by individual, trophozoite‐stage Plasmodium falciparum cells expressing a chondroitin sulphate A binding phenotype

Abstract: Summary In this study, we detected multiple var gene transcripts within single, mature trophozoite‐infected red blood cells (iRBCs) bound to chondroitin sulphate A (CSA). Several of the var detected had previously been demonstrated to encode Plasmodium falciparum erythrocyte membrane protein‐1 (PfEMP‐1) variants with domains that mediated iRBC adhesion to receptors other than CSA. Parasites expressing the CSA‐adherent phenotype transcribed far more of one var than of all others, but this gene was differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
67
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 31 publications
6
67
0
1
Order By: Relevance
“…1b). Using the analysis of Taylor et al (39), these degenerate primers showed a low bias towards amplification of the most frequently detected sequence of Ͻ2% (since 1.02 40 is Ͼ1.5), which is consistent with those of other "universal" DBL domain degenerate primers (8,24,38). Nevertheless, the bias may prevent the amplification of some DBL␥ sequences.…”
Section: Resultssupporting
confidence: 73%
“…1b). Using the analysis of Taylor et al (39), these degenerate primers showed a low bias towards amplification of the most frequently detected sequence of Ͻ2% (since 1.02 40 is Ͼ1.5), which is consistent with those of other "universal" DBL domain degenerate primers (8,24,38). Nevertheless, the bias may prevent the amplification of some DBL␥ sequences.…”
Section: Resultssupporting
confidence: 73%
“…The bestcharacterized VSA, P. falciparum erythrocyte membrane protein 1 (PfEMP1), mediates cytoadherence and antigenic variation (4,41,44). PfEMP1 is encoded by 50 to 60 var genes per haploid parasite genome (15,39,44,45), but only one or a few genes are expressed by each parasite at any given time (12,14,34,45,48). The availability of the complete genome sequence of P. falciparum laboratory clone 3D7 (16) and the ability to select 3D7 for VSA SM -like expression (43) have made it possible to identify the group A var genes likely to code for VSA SM types (21,25,28).…”
mentioning
confidence: 99%
“…Binding to CSA has been localized to DBL␥ domains of these genes (12,18,32,38,43,44). However, recent studies of FCR3varCSA failed to show a correlation between transcription and the CSA adhesion phenotype or specific transcription in placental-type parasites (21,27,35,47). FCR3varCSA (12,50) and varCS2 (43) were originally identified in CSA-adherent parasite lines using reverse transcription PCR (RT-PCR).…”
mentioning
confidence: 99%
“…FCR3varCSA (12,50) and varCS2 (43) were originally identified in CSA-adherent parasite lines using reverse transcription PCR (RT-PCR). Since single trophozoites can transcribe multiple var genes simultaneously (21), this approach might detect genes that do not encode the expressed PfEMP1 protein.…”
mentioning
confidence: 99%